Pemberdayaan Ekonomi Rumah Tangga Melalui Pelatihan Pembuatan Deterjen Sabun Pencuci Piring Ramah Lingkungan - Irdamurni, Irdamurni; Ardisal, Ardisal; Isma, Teguh Wijaksana (Civiliza Publishing, 2024)
Community participation in developing the regional economy is needed. However, with the current condition, people are confused about where to start their business and what kind. Through community service lecturers on training in making dishwashing detergents, it is hoped that this can reduce the burden on the community. Dish washing soap is one of the household necessities which functions as a remover of dirt and grease on eating and cooking utensils. The continuous consumption of dish soap every day causes the need to procure soap at a cost that is not small, especially for women in RT 2 RW 4 Kelurahan Koto Lua Sub-district Pauh Padang. The purpose of carrying out this community service is to provide knowledge and training to mothers about making liquid dish soap in order to reduce community expenditure on purchasing soap as well as to create new business opportunities. In the service activity, the raw materials, work procedures and production costs for making dish soap will be explained. From the activities carried out, partners can produce product output in the form of liquid dish soap according to the method given in the training. The results obtained by training participants were able to recognize ingredients and be able to make dishwashing detergent and increase the skills of mothers in making dishwashing detergent.